Stimulation of particle-induced chemiluminescence in human granulocytes by various Escherichia coli strains. - Falkenhagen, U. (1986)
The patterns of neutrophil chemiluminescence stimulated by groups of E. coli strains opsonized with pooled normal human serum were compared. All strains of E. coli were obtained from patients with chronic pyelonephritis. 'O' serovars which lacked capsular (K) antigen produced significantly higher chemiluminescence than strains possessing a variety of K antigens. Chemiluminescence produced by a range 'O' serovars bearing the K1 antigen did not differ significantly from those containing other K antigens. The lowest chemiluminescence values were obtained with a group of O2:K1 strains. Rough strains containing K1 antigen were also poor stimulators of chemiluminescence.